A novel flame retardant derived from DOPO and piperazine and its application in epoxy resin: Flame retardance, thermal stability and pyrolysis behavior. (August 2019) - Chen, Rui; Hu, Kaixian; Tang, Hao; Wang, Junjie; Zhu, Fusheng; Zhou, Hong
Abstract: A novel flame retardant poly (piperazine phosphaphenanthrene) (DOPMPA) was successfully synthesized via two step reactions using DOPO and piperazine as reactants and characterized by infrared spectrometry (FT-IR), nuclear magnetic resonance (NMR) and gel permeation chromatography (GPC). The DOPMPA was used to enhance flame retardancy of epoxy resin (EP). When the addition content of DOPMPA in EP was 13 wt%, the EP/DOPMPA sample passed a UL-94 V-0 rating and possessed a high limited oxygen index (LOI) value of 34%. Cone calorimeter tests showed that the release of heat and smoke for EP/DOPMPA samples decreased significantly compared with neat EP. Moreover, the reduction of average effective heat of combustion (av-EHC) value with the increased addition of DOPMPA confirmed that DOPMPA had a flame-inhibition activity in gashouse phase. The analysis of the char residues after cone calorimeter test exhibited that DOPMPA promoted the swell of the sample and compacted char layer. Furthermore, the pyrolysis analysis of DOPMPA was investigated by pyrolysis-gas chromatography/mass spectrometry (Py-GC/MS), which illustrated that DOPMPA decomposed into many fragments with quenching effect toward combustion. Highlights: A novel flame retardant (DOPMPA) containing DOPO and piperazine structure was synthesized. DOPMPA endowed EP with excellent fire safety. DOPMPA played a flame-retardant role in both condensed and gaseous phases.